2011
DOI: 10.1007/s10847-011-9990-x
|View full text |Cite
|
Sign up to set email alerts
|

NSAID naproxen in mesoporous matrix MCM-41: drug uptake and release properties

Abstract: Hexagonally ordered mesoporous silica material MCM-41 (S BET = 1090 m 2 /g, pore size = 31.2 Å) was synthesized and modified by 3-aminopropyl ligands. The differences in an uptake and subsequent release of anti-inflammatory drug naproxen from unmodified and amino modified MCM-41 samples were studied. The prepared materials were characterized by high resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM), nitrogen adsorption/desorption, Fourier-Transform Infrared Spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…66 For example, surfactants such as hexadecyltrimethylammonium bromide (C 16 TAB) and dodecyltrimethylammonium bromide (C 12 TAB) are important in controlling pore size, particle morphology and thus loading dose. 61,64,99 The longer chain length of C 16 TAB used in MCM-41 increased pore size and released high dose of therapeutic agent, ibuprofen (68%), than shorter chain length of C 12 TAB, which only released 55% of ibuprofen. 66 Similarly, the addition of surfactant, N -cetyltrimethylammonium bromide (CTAB), prolonged the release of cancer agents, which enhanced the effects of cytotoxicity.…”
Section: Currently Available Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…66 For example, surfactants such as hexadecyltrimethylammonium bromide (C 16 TAB) and dodecyltrimethylammonium bromide (C 12 TAB) are important in controlling pore size, particle morphology and thus loading dose. 61,64,99 The longer chain length of C 16 TAB used in MCM-41 increased pore size and released high dose of therapeutic agent, ibuprofen (68%), than shorter chain length of C 12 TAB, which only released 55% of ibuprofen. 66 Similarly, the addition of surfactant, N -cetyltrimethylammonium bromide (CTAB), prolonged the release of cancer agents, which enhanced the effects of cytotoxicity.…”
Section: Currently Available Drug Delivery Systemsmentioning
confidence: 99%
“…In addition, due to the additional interaction between amine group and naproxen, sustained release of naproxen was observed in amine-modified MCM-41. 99 …”
Section: Currently Available Drug Delivery Systemsmentioning
confidence: 99%
“…However, the drug release rate is comparable and studies show that the drug release rate is within the range of reported results in other articles. The amounts of the released naproxen from amine‐modified and native MCM‐41 mesoporous silica were 90 and 95% of naproxen after 72 h . Naproxen release from chitosan/carbon nanotube nanocomposite hydrogel reached at 50–60% after 72 h at pH 7.4…”
Section: Resultsmentioning
confidence: 99%
“…MCM-41 and SBA-15 are two common mesoporous silica materials, which have different pore sizes, including 2-5 nm and 5-10 nm, respectively. The smaller pore size helps to slow drug release and provides higher stability in mesoporous silica NPs [98,97,92]. In addition, the surface functionalization of silica NPs with different molecules allows developing silica NPs with various surface properties [96,99].…”
Section: Mesoporous Silica Nanoparticles (Msn)mentioning
confidence: 99%